Effect of Astragaloside IV on improving cardiac function in rats with heart failure: a preclinical systematic review and meta-analysis - Zhang, Zhiyuan; Zhang, Muxin; Xu, Yongkai; Lu, Mengkai; Zhang, Lei; Li, Chao (Frontiers in Pharmacology, 2023)
Background: Astragaloside IV (ASIV) is the primary pharmacologically active compound found in Astragalus propinquus Schischkin, which has potential protective effects on cardiac function. However, there are almost no systematic evaluations of ASIV for the treatment of heart failure (HF).Methods: Preclinical studies published before December 27th, 2022, were retrieved from PubMed, Web of Science, MEDLINE, SinoMed, Chinese National Knowledge Infrastructure (CNKI), VIP information database, and Wanfang Data information site. The quality of included research was evaluated using SYRCLE's RoB tool. Review Manager 5.4.1 was used to perform meta-analyses of the cardiac function parameters and other indicators. Regression analysis was conducted to observe the dose-efficacy relationship.Results: Nineteen studies involving 489 animals were included. Results indicated that compared with the control group, ASIV could enhance cardiac function indicators, including left ventricular ejection fraction (LVEF), left ventricular fractional shortening (LVFS), left ventricular pressure change rate (± dp/dtmax), left ventricular end-diastolic pressure (LVEDP), left ventricular systolic pressure (LVSP), heart weight/body weight (HW/BW) and left ventricular weight/body weight (LVW/BW). Furthermore, the regression analysis showed that the treatment of HF with ASIV was dosedependent.Conclusion: Findings suggest that ASIV can inhibit cardiac hypertrophy by reducing cardiac preload and afterload, thereby protecting cardiac function.